2001
DOI: 10.1136/adc.85.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral gangrene during infancy: a rare presentation of systemic lupus erythematosus

Abstract: An 11 month old boy presented with gangrene of the extremities. He was found to have positive nuclear antibodies and antibodies to double stranded DNA, and negative Ro and La antibodies. The infant was started on oral prednisolone, which was discontinued after six months. At one year of follow up he was asymptomatic, with negative nuclear antibodies and antibodies to double stranded DNA. (Arch Dis Child 2001;85:335-336)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…It is rare to have digital gangrene in children below the age of five years. Yet, it is worth mentioning that there has been one report of digital gangrene in infancy [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is rare to have digital gangrene in children below the age of five years. Yet, it is worth mentioning that there has been one report of digital gangrene in infancy [7].…”
Section: Discussionmentioning
confidence: 99%
“…In SLE a variety of clinical manifestations such as Raynaud’s phenomenon, acrocyanosis, livedo patterns, erythematous or violaceous macules, and papules or necrosis are triggered by heterogeneous pathophysiological mechanisms such as vasospasm, vasculitis, or thromboembolism. Gangrene of the extremities is very rare, occurring in about 1% of SLE patients, and most often affects the upper extremities [8]. Endarteritis, although rare, is an important complication of SLE, in which vasculopathy affects arteries in the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Shetty et al reported the first case of SLE presenting with foot and hand gangrene in a neonate [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gangrene is an exceptionally rare form of SLE cutaneous manifestations, accounting for 1.4% of SLE patients [2]. SLE gangrene most often affects the upper extremities and involves no more than the digits [3]. Pathophysiology underlying SLE gangrene includes vasospasm, thromboembolism, and vasculitis [4].…”
Section: Introductionmentioning
confidence: 99%